Do management earnings forecasts incorporate information in accruals? - Xu, Weihong (Journal of Accounting and Economics, 2010)
I investigate whether management earnings forecasts fully reflect the implications of accruals for future earnings. I find that managers overestimate accrual persistence in range forecasts but not in point forecasts and that managers’ accrual-related forecast bias in range forecasts increases with forecast range and forecast horizon. My results suggest that managers overestimate accrual persistence when faced with greater difficulty forecasting earnings. Moreover, I find that managers’ accrual-related forecast bias in range forecasts is somewhat affected by managerial opportunism and fear of litigation. Finally, I find accrual mispricing for firms issuing range forecasts but not for firms issuing point forecasts.